Evaluation of public participation in carbon sequestration project in Ghahavand plain - Behnaz Ataeian; Reza Alvandi (مطالعات جغرافیایی مناطق خشک)
Aim: This study aims to find out how involved the local population is in the effort to combat desertification and give local residents' opinions more weight so that they may be considered when making decisions at the local and regional levels. Materials & Methods: This descriptive-correlation study was carried out in the customary systems of the Qahavand area of Hamadan. Sampling was done using a basic random approach, and the number of samples was calculated using Cochran's formula of 53 operators. A questionnaire was used as the study technique, and direct interviews with regional operators were conducted to complete it. Descriptive and inferential analysis was performed using SPSS 16 software. Finding: The Kruskal Wallis and Pearson test results revealed that the factors of the number of dependents, the amount of income, the level of literacy, and the highest level of participation in livestock farmers with more than 150 animals all have a positive and significant effect on farmers' participation in pasture sustainability management. As a result, as the number of dependents grows, so do the beneficiaries' literacy levels, livestock numbers, and income. Conclusion: Based on the findings, it is clear that stakeholder participation in the rehabilitation, administration, and implementation of natural resource initiatives is critical to the success of management projects. Specialists (executive authorities) play a role in improving natural ecosystems, but stakeholders play a more essential role. Consequently, any attempt to increase communication and collaboration between these two groups will ensure that rangeland rehabilitation is carried out within the framework of sustainable development. Innovation: The carbon sequestration project is intended to address one of Iran's development priorities for desertification and create a cooperative management model for rangelands in arid and semi-arid areas, with the goal of reducing poverty and increasing carbon absorption; thus, as a priority program, it addresses both global environmental protection issues and national development priorities.